PERSPEKTIF FIQIH TERHADAP LINGKUNGAN - Faiz Zainuddin (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2021)
Fiqh as Islamic law that regulates the pattern of human relations with God and each other, takes part in discussing the relationship between humans and their environment. The role of fiqh in the matter of efforts to maintain environmental harmony by providing rules or codes of ethics for human relations with their environment. Such as the prohibition of damaging the environment and the obligation to preserve the environment. The arrangement of environmental law is based on tafsiliy arguments, namely al-Qur'an-al-Hadith, and general principles of legal legislation. When fiqh takes part in environmental preservation, it is hoped that there will be new awareness for all mukallaf, especially awareness related to environmental problems. They have a high concern for the environment. Giving rights that belong to the environment, such as the right to live and the right to develop, not to seize and exploit. That way the environment remains sustainable, beautiful and conducive. Humans and all other creatures will peacefully inhabit this rice field. There is no longer the threat of global catastrophe that currently haunts people's days.